Marketing Strategy in Maintaining the Continuity of Micro, Small and Medium Enterprises (MSMEs) during the Covid-19 Pandemic in Pekanbaru City - Gatot Wijayanto; Jushermi Jushermi; Marzolina Marzolina; Arwinence Pramadewi; Rovanita Rama (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
This research is a literature study on marketing strategies for MSME owners in Riau. This study aims to analyze what marketing strategies are used by MSME owners in an effort to maintain their business continuity. The research method used in this study is a qualitative descriptive method. The type of data used in this study is qualitative data, which is categorized into two types, namely primary data and secondary data. Sources of data obtained through library research techniques (library study) which refers to sources available both online and offline such as: scientific journals, books and news sourced from trusted sources. The results of the study conclude that the marketing strategies carried out by MSME owners in maintaining their business during the Covid-19 pandemic are; Product Strategy, during the Covid-19 pandemic, MSME owners in Riau also created innovations in their respective products. Price Strategy (Price), during the pandemic, MSME owners in Riau also carried out a price strategy in the form of discounts or price discounts to attract consumers and be able to maintain business. Promotion Strategy (Promotion), The forms of promotion used are: (1) Advertising (Advertising) (2) Personal Selling (Personal Selling) (3) Sales Promotion (4) Place Strategy (Place/Distribution).